Analisis Normatif: Kerugian yang Ditimbulkan oleh Penggunaan Alat Tangkap Ikan Pukat Harimau terhadap Kelestarian Lingkungan - Muhammad A. Rauf; Mukhlis R; Davit Rahmadan; Sukamarriko Andrikasmi (Riau Law Journal, 2024)
Good management of regional assets is also key in improving financial capabilities and services to the community. The legal basis for regional asset management is regulated in Government Regulation Number 27 of 2014, which emphasizes the importance of administrative, physical and legal security for regional property. Thus, regional heads have a big responsibility in managing regional assets to avoid disputes and maximize the potential of assets as regional wealth. Management of regional assets, especially land, often faces various challenges, including unclear ownership status, lack of adequate documentation, and protracted legal conflicts. This study aims to identify the factors that cause disputes over regional land assets and evaluate the effectiveness of administration and control carried out by the regional government. In this research we will examine the problems of administering and controlling regionally owned land which is the object of dispute in court (goods management study belonging to a region in the province of Riau, the type of research used is research in the form of an empirical study which is to find theories regarding the process of occurrence and operation of law in society which finds facts according to what happened as they are, the conclusion of this research is Problematics The administration and control of BMD in Riau Province is caused by a lack of commitment from the relevant institutions and the high interest of third parties who have bad intentions, which often results in disputes in court. Although the courts generally uphold the rights of the Riau Provincial Government, this problem still affects the recording and reporting of regional assets